2004
DOI: 10.1037/0021-9010.89.6.1099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Polygraph Data Obtained From Individuals Involved in Mock Crimes and Actual Criminal Investigations.

Abstract: In a preliminary attempt to determine the generalizability of data from laboratory mock-crime studies, the authors examined the similarities and differences among the cardiovascular, electrodermal, and respiration responses of deceptive and nondeceptive individuals elicited to crime-relevant and crime-irrelevant questions. Participants in the laboratory group were randomly assigned to nondeceptive (n = 28) or deceptive (n = 27) treatment groups, and a mock-crime scenario was used. The field participants were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 17 publications
(19 reference statements)
1
20
0
Order By: Relevance
“…Although this conclusion is based on consistently larger effect sizes in laboratory settings than in the field, examining the influence of this difference on detection efficiency is less common. However, a recent study by Pollina, Dollins, Senter, Krapohl, and Ryan (2004) replicated this effect size difference, but showed that it did not influence test accuracy or diagnosticity. Similarly, Ben-Shakhar and Elaad (2003) conducted a large meta-analysis of GKT studies and found a significant difference in effect size when 'highly motivated' participants (d ¼ 1.76) were compared to those with 'low motivation' (d ¼ 1.34), but not on their respective test efficiencies (a ¼ .82 and .80, respectively).…”
Section: Discussionmentioning
confidence: 90%
“…Although this conclusion is based on consistently larger effect sizes in laboratory settings than in the field, examining the influence of this difference on detection efficiency is less common. However, a recent study by Pollina, Dollins, Senter, Krapohl, and Ryan (2004) replicated this effect size difference, but showed that it did not influence test accuracy or diagnosticity. Similarly, Ben-Shakhar and Elaad (2003) conducted a large meta-analysis of GKT studies and found a significant difference in effect size when 'highly motivated' participants (d ¼ 1.76) were compared to those with 'low motivation' (d ¼ 1.34), but not on their respective test efficiencies (a ¼ .82 and .80, respectively).…”
Section: Discussionmentioning
confidence: 90%
“…Hence, they were not exposed to the real threat confronting suspects undergoing real GKT examinations. This may lead on the one hand to the desire of guilty examinees, who believe that the GKT is designed to detect deception, to ''win the game'' by increasing attention to the relevant questions (Pollina et al, 2004). On the other hand, this may lead to a neglect of the relevant items, which are related to unreal crimes.…”
Section: Discussionmentioning
confidence: 98%
“…This might be because the choice of whether to perform a morally sanctioned act of deception in a game and the more morally loaded choice of whether to break a promise, involve different social phenomena – rejection (van Beest and Williams, 2006) and guilt respectively. Nevertheless, it is challenging to evoke and accurately assess guilt associated with deception in real-life interrogations (Bashore and Rapp, 1993; Pollina et al, 2004), let alone in experimental settings.…”
Section: Discussionmentioning
confidence: 99%